Importación de calzado chino y su impacto en la producción de las mypes del sector calzado- distrito El Porvenir: 2019 - Alfaro Carranza, Flor (2021)
This investigation was developed with the purpose of: Determining how Chinese footwear imports impact on the production of MYPES in the footwear sector in the El Porvenir: 2019 district, starting from the problem: How do Chinese footwear imports impact on the production of the MYPES of the footwear sector-El Porvenir District: 2019? The proposed hypothesis: Chinese footwear imports significantly impact the production of the MYPES of the footwear sector in the El Porvenir district: 2019. This study carried out in the footwear sector used the correlational-cross-sectional design, which had a population of 1051 Shoe Mypes in the El Porvenir District. To collect the information, we used the survey as a technique, and the questionnaire as an instrument, which was applied to a sample of 109 Mypes and was validated by the Cronbach coefficient, where for the importation of footwear it was 0.9968 and for the production of the Mypes of 0.9930. To determine the influence between the two variables under study, we used Pearson's coefficient, which indicated a correlation of 0.912. Finally, it was concluded that the Importation of Chinese footwear had a negative and significant impact on the production of MSEs in the footwear sector during 2019, so the main footwear producers in the District have to improve their manufacturing and distribution strategies.